2003
DOI: 10.21273/jashs.128.3.0374
|View full text |Cite
|
Sign up to set email alerts
|

Developing Microsatellite DNA Markers in Pecan

Abstract: A microsatellite-enriched library was developed from `Halbert', a native pecan [Carya illinoinensis (Wangenh.) K. Koch] selection from Coleman County, Texas. A genomic library enriched for simple sequence repeats (SSR) containing 6144 clones was archived in 384 well plates for screening. In total, 439 clones were identified after Southern hybridization using di- and tri-nucleotide repeats as probes. In total, 125 positive clones were sequenced and primers were designed for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…The thermal cycling protocol consisted of 3 min at 94°C followed by 35-40 cycles of 45 s at 94°C, 45 s at 55 C and 1 min at 72°C, and final elongation of 40-60 min at 72°C. In addition, 14 nuclear microsatellites (Grauke et al 2003, Mendoza-Herrera et al 2008, including six previously identified in Juglans (Woeste et al 2002;Dangl et al 2005) were amplified for the 80 accessions. After PCR, 3 μl of each sample was loaded in a 2% agarose gel in 1× TAE buffer and stained with ethidium bromide to verify amplification.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal cycling protocol consisted of 3 min at 94°C followed by 35-40 cycles of 45 s at 94°C, 45 s at 55 C and 1 min at 72°C, and final elongation of 40-60 min at 72°C. In addition, 14 nuclear microsatellites (Grauke et al 2003, Mendoza-Herrera et al 2008, including six previously identified in Juglans (Woeste et al 2002;Dangl et al 2005) were amplified for the 80 accessions. After PCR, 3 μl of each sample was loaded in a 2% agarose gel in 1× TAE buffer and stained with ethidium bromide to verify amplification.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular profiles have been developed for many accessions in the collection using 14 nuclear microsatellite markers and 3 plastid markers (Grauke et al 2003, 2010, 2015). Immature leaflets are harvested from specific inventories and frozen at −80 °C until DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…AFLPs can be converted to SCARs by using the same basic method as for RAPD-PCR. To improve the economic value of B. platyphylla, Wang et al (2008a) used RAPD and SCAR to analyze birch trees with the greatest fiber length for use in the selective breeding process, while Grauke et al (2003) explored microsatellites and SSRs for improved scoring and resolution within pecan.…”
Section: Marker Technologies In Conservation and Tree Improvementmentioning
confidence: 99%
“…American chestnut has been transformed to express the wheat germin-like oxalate oxidase gene in an effort to bolster its resistance to fungal pathogens (Welch et al 2007). With hardwood genetic modification, Gao and Jiang 2009;Howland et al 1995;Jiang et al 2007;Kulju et al 2004;Schenk et al 2008;Truong et al 2007;Wang et al 2008a;Wang et al 2008b Carya AFLP, isozymes, microsatellites, SSR Beedanagari and Conner 2004;Beedanagari et al 2005;Grauke et al 2003;Rϋter et al 1999;2000;Vendrame et al 2000 Castanea AFLP, isozymes, ISSRs, microsatellites, QTL, RFLP, RAPD, SSR Barakat et al 2009;Batista et al 2008;Buck et al 2003;Casasoli et al 2004;Casasoli et al 2006;Clark et al 2001;Feng et al 2007;Marinoni et al 2003;Sisco et al 2005Sisco et al , 2009Tanaka et al 2005; RAPD Buiteveld et al 2007;Jump and Peñuelas 2007;Kraj and Sztorc 2009;Sander et al 2000;Scalfi et al 2004;Scalfi et al 2005;Sisco et al 2009;Vornam et al 2004 Fraxinus Microsatellites, RAPD, RFLP Bacles and Ennos 2008;Harbourne et al 2005;Heuertz et al 2003;Heuertz et al 2004;Lefort et ...…”
Section: Genomic Tools and Genetic Engineering In Hardwood Tree Impromentioning
confidence: 99%